PEMBUATAN DISPENSER DESTILASI AIR LAUT SEBAGAI SARANA SUMBER AIR TAWAR UNTUK DAERAH PESISIR PANTAI - Engkos Koswara; Nasim Nasim (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Currently, the national water demand is concentrated in Java and Bali, with the purpose of using it mainly for drinking water, household, urban, industrial, agricultural, and others. From the 2003 water balance data, it can be seen that the water demand in the dry season in Java and Bali, which amounted to 38.4 billion cubic meters, was only met by about 25.3 billion cubic meters or only about 66 percent. This deficit is expected to be even higher in 2020, where the population and economic activity will increase significantly. (Directorate of Irrigation and Irrigation Bappenas, 2006). Without exception, coastal areas are also in dire need of clean water. Because of its position with the sea, it is very possible for sea water intrusion to occur so that freshwater sources will be affected by sea water. Therefore, coastal areas are in dire need of fresh water. In this study, it will be studied how to make a simple Sea Water Distillation Dispenser that can be owned by each house. It is hoped that in this way, every citizen will have facilities to provide clean water. The highest temperature of the reactor is 70